Radiative cooling of cationic carbon clusters, CN+, N = 8, 10, 13–16. Issue 3 (8th January 2019) - Chen, F.-Q.; Kono, N.; Suzuki, R.; Furukawa, T.; Tanuma, H.; Ferrari, P.; Azuma, T.; Matsumoto, J.; Shiromaru, H.; Zhaunerchyk, V.; Hansen, K.
Abstract : Measured photon emission rate constants from thermally excited electronic states of small carbon cation clusters. Abstract : The radiative cooling of highly excited carbon cluster cations of sizes N = 8, 10, 13–16 has been studied in an electrostatic storage ring. The cooling rate constants vary with cluster size from a maximum at N = 8 of 2.6 × 10 4 s −1 and a minimum at N = 13 of 4.4 × 10 3 s −1 . The high rates indicate that photon emission takes place from electronically excited ions, providing a strong stabilizing cooling of the molecules.